Impairments of Visuospatial Attention in Children with Unilateral Spastic Cerebral Palsy - Ickx, Gaétan (Neural plasticity, 2018)
Aim: This observational study aimed at assessing the prevalence of visuospatial attention deficits in children with unilateral spastic cerebral palsy (USCP), taking into consideration the affected hemibody and the localization of the brain lesion